Assessment of sweet potato (Ipomoea batatas) accessions for growth, yield and quality traits - PAVITHRA, P; THANGAMANI, C; PUGALENDHI, L; KUMAR, J SURESH (The Indian Journal of Agricultural Sciences, 2023)
From the study it was noticed that winter sweet potato crop (first season) recorded higher tuber yield due to more utilization of photosynthates, and optimum temperatures for tuberisation and tuber bulking. Second season crop (summer to early monsoon crop) recorded higher vegetative growth which was due to more sunlight and higher temperatures during the crop period which promoted vegetative growth. The pooled analysis of two season’s data revealed that genotype Ib 73 recorded higher tuber length, number of tubers per vine, single tuber weight, tuber yield/vine and marketable tuber yield per hectare, maximum dry matter content, which had a positive correlation with tuber yield. Less weevil infestation percentage was recorded in Ib 73, it might be due to the characteristic feature of thin vine with more latex content. One of the important quality parameters is β-Carotene content in the tuber, which was recorded maximum in the variety Sree Kanaka, thus it may be recommended for the alleviation of malnutrition in children. However, Ib 73 excelled other genotypes in terms of yield and cooking quality characters with low TSS and total sugar content, hence it can be recommended for commercial cultivation among the farmers by replacing potatoes for culinary purpose.